Revolutionizing Listening Practice: Integrating Autoproctor Google Forms for Scalable English Learning in Large EFL Classrooms - Muchamad Arif; Gunarti Dwi Lestari; Widodo; Andi Kristanto; Varia Virdania Virdaus; Anahita Ghanad (Journal of Pedagogy and Education Science, 2026)
This study explores the integration of AutoProctor-enabled Google Forms to enhance English listening comprehension in large EFL classrooms. The research aims to address challenges of academic integrity and scalability faced by university instructors in technology-limited contexts. Employing a descriptive mixed-method design, data were collected from 95 undergraduate students and one lecturer through questionnaires and semi-structured interviews. The results indicate that the integration of AutoProctor in listening activities improved students’ motivation, confidence, and comprehension, while also ensuring a fair testing environment through automated proctoring features. Participants appreciated the platform’s automated grading, immediacy of feedback, and accessibility for independent practice. However, technical limitations such as unstable connectivity and restricted access to premium features occasionally constrained learning efficiency. The study highlights that AutoProctor-based Google Forms constitute a viable and integrity-oriented innovation for large-scale English learning, supporting both learner autonomy and sustainable digital pedagogy. The findings also offer implications for the broader use of AI-assisted assessment in EFL instruction.